Congenital Absence of Left Circumflex Artery: A Case Report and Review of the Literature - Setri Fugar; Lydia Issac; Alexis Kofi Okoh; Christelle Chedrawy; Nadia El Hangouche; Neha Yadav (Case Reports in Cardiology)
Congenital absence of the left circumflex artery is a rare coronary anomaly with few reported cases in the literature. These patients are usually diagnosed incidentally when they undergo coronary angiography or coronary CT to rule out underlying coronary artery disease. In this article, we report a case of a 46-year-old man who was incidentally found to have a congenitally absent left circumflex artery with a superdominant right coronary artery after a workup was initiated for frequent premature ventricular contractions and regional wall motion on echocardiogram. A review of the clinical presentation, symptoms, and diagnostic modalities used to diagnose this entity is presented.